The Urgency of Legal Protection for Domestic Workers as Informal Workers - Sherlyn Nathalia Cheung; Yuwono Prianto; Sheren Hardjono (Unnes Law Journal, 2023)
One of the informal professions in Indonesia is a domestic worker. The problem is that domestic workers have not received maximum protection related to their wages, comfort and work safety which causes them belittled because the lack of their awareness about the rights they supposed to get. This article was made to examine the issues faced by domestic workers and what steps can be taken to improve the bargaining position of domestic workers. The research method used is empirical sociological, focusing on primary data and interviews, supported by secondary data. Data collection and analysis were carried out qualitatively by using Anthon F. Susanto model through the stages of data triangulation. The conclusion is that in Government Regulation Number 2 of 2015 there are no details regarding the rights of domestic workers and there are no laws protecting domestic workers so there are still many violations against domestic workers.